Population Growth and Automation Density: Theory and Cross-Country Evidence - Ana Lucia Abeliansky; Klaus Prettner (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2021)
We analyse the effects of declining population growth on automation. Theoretical considerations imply that countries with lower population growth introduce automation technologies faster than those with higher population growth. We test the theoretical implication on panel data for 60 countries over the time span 1993-2013. Regression estimates support the theoretical implication, suggesting that a one percent increase in population growth is associated with an approximately two percent reduction in the growth rate of robot density. Our results are robust to the inclusion of standard control variables, different estimation methods, dynamic specifications, and changes with respect measuring robot stocks.
Keywords: 300; Automation; Industrial Robots; Demographic Change; Declining Fertility